ADVANCING THE METHODOLOGY OF TEACHING BIOLOGICAL SCIENCES BASED ON THE ORGANIZATION OF RESEARCH ACTIVITIES OF STUDENTS - Khamdamova, M. (Farabi Journal of Social Sciences, 2022)
At the present time, the most important task of higher education is its focus on the acquisition of each student’s own full-fledged personal experience. In this regard, a number of presidential decrees and orders will be adopted in the coming years, raising the education system to a new, higher level. Special attention is paid to the improvement of teaching methods, the gradual introduction of the principles of individualization of the educational process, the introduction of modern information and communication technologies and innovative projects in the field of higher education. Based on all of the above, going beyond the profile of our activities, as well as the scientific goal, our attention was drawn to the organization of research activities in the teaching of biological sciences. In the work under study, the terminological apparatus of the definition of the concept of "research activity" was given, which is presented by local authors, researchers from CIS countries and foreign authors. In the course of carrying out research activities, projects developed by us were provided, such as: Conducting a laboratory lesson on the topic: Studying the results of crossing cotton, tomato and night beauty plants based on a herbarium; Organizing a study tour on the topic: Studying genetically resistant cotton varieties (Bukhara 6, Porlok); Organizing a school scientific and practical conference on the topic "Hereditary diseases in humans". At the end of the research work, an experimental study monitoring the effectiveness of the organization of research activities in the teaching of biological sciences is presented. Keywords: education, pedagogical higher educational institutions, research activities.